Start by finding the first differences of the terms:

\[

\begin{array}{ll}

\text { For } T_{1} \text { and } T_{2}: & -15-(-7)=-8 \\

\text { For } T_{2} \text { and } T_{3}: & -25-(-15)=-10 \\

\text { For } T_{3} \text { and } T_{4}: & -37-(-25)=-12

\end{array}

\]

Now calculate the second differences:

\[

\begin{array}{ll}

\text { first two differences: } & -10-(-8)=-2 \\

\text { next two differences: } & -12-(-10)=-2

\end{array}

\]

In this case, the second differences are equal to each other, with a value of \(-2\).